THE HUMANISTIC APRROACH TO CHANGE AND THE DEVELOPMENT OF BEHAVIOR IN THE REALM OF EDUCATION - Pebri Yanasari (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2016)
Learning is a view of the basic of human development. With study, human life and working according to what has been learned to make changes yourself so that behavior can develop. It is said in the learning theories of humanistic man that can be essentially learned in a natural manner capable of adjusting to all the changes that have or are happening in the surrounding. Therefore,  as the educator who is the executor is important in the process of learning to interpret his position as a wise parent  who can understand what the needs of the needs of the students in their studies, both methodologically and based on the subject matter that will be given to students. If such a case is well understood by teacher, then it will have a positive impact  not only for teachers but for students themselves. To teachers course, students will sympathize to follow the activies of learning from his teacher. And students will easily understand the teaching materials well because the teachers strategies and subject matter in accordance with the call of his soul. Moreover, in the aspect of its application, learning theory humanistic learning in the teacher is directing  the students to think induktif attach great importance to experience and  foster student engagement scara  is active  in the learning  process. This study, using the approach of humanist and  textual.  Learning  theory humanist is the  concept of learning  is looking  at the  development of the  human personality.  Focusing  on the human potential to seek and find skills they have and develop those  abilities.